Effect of KNO₃ Fertilizer Concentration Levels on the Growth and Yield of Butternut Squash (Cucurbita moschata) - Arin Maulani Sya'bana; Budiman Budiman; Tubagus Kiki Kawakibi Azmi (Jurnal Biologi Tropis, 2026)
Butternut squash (Cucurbita moschata) is a fruit rich in nutrients, especially carbohydrates, making it a potential alternative food source. Optimal growth of this plant can be achieved through fertilization, such as with potassium nitrate (KNO₃), which contains potassium and nitrogen to enhance growth, quality, and yield. This study aimed to determine the effect of different KNO₃ fertilizer concentrations on the growth and yield of butternut squash plants. The research was conducted from February to June 2025 at Kebun Bibit Cibubur Pusat Pengembangan Benih dan Proteksi Tanaman (P2BPT), Jl. Jambore, Cibubur, Ciracas District, East Jakarta City. The experiment used a Randomized Complete Block Design (RCBD) with a single factor, namely KNO₃ concentration, consisting of five treatment levels: K0 (control), K1 (8 g/L), K2 (16 g/L), K3 (24 g/L), and K4 (32 g/L). Each treatment was replicated six times with two samples per replicate, resulting in 30 experimental units and a total of 60 plant samples. The observed parameters included plant height (cm), number of leaves (leaves), stem diameter (mm), fruit weight (g), fruit diameter (cm), fruit length (cm), flesh thickness (cm), and fruit sweetness (°Brix). Data were analyzed using analysis of variance (ANOVA) by The SAS System for Windows 9.0, followed and further testing using Duncan’s Multiple Range Test (DMRT) at a significance level of α = 5%. The results showed that KNO₃ fertilizer had a significant effect on the growth and yield of butternut squash, particularly on plant height at 6–8 weeks after transplanting (WAT), number of leaves at 5–8 WAT, and fruit weight. The highest growth and yield were obtained at the concentration of 32 g/L KNO₃.